PENGEMBANGAN GAME PEMBELAJARAN INTERAKTIF MATEMATIKA BANGUN RUANG SISWA KELAS 6 SD - ahmad zainudin; Agus priyadi; Andik Prakasa Hadi; ALDO KRISDIANANTA (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
Mathematics is one of the important subjects. Mathematics is also a subject that is difficult to understand. Understanding concepts is the most important part of learning mathematics, meaning that in studying mathematics students must first understand mathematical concepts in order to be able to solve problems and be able to apply this learning in the real world. Based on direct observations and interviews with grade 6 teachers at SD Negeri 02 Getas, teachers have difficulties in the theme of lesson 3 about "Building Space" with basic competencies; 1) identify & compare geometric shapes; 2) calculating the surface area of the geometric shape; 3) calculate the volume of the geometric shape. This is what drives the need to develop game-based mathematics learning media. This game was created using Construct2 software as a 2D video game engine. The method used in this study is the MDLC (Multimedia Development Life Cycle) method. Mathematics is one of the important subjects. Mathematics is also a subject that is difficult to understand. Understanding concepts is the most important part of learning mathematics, meaning that in studying mathematics students must first understand mathematical concepts in order to be able to solve problems and be able to apply this learning in the real world. Based on direct observations and interviews with grade 6 teachers at SD Negeri 02 Getas, teachers have difficulties in the theme of lesson 3 about "Building Space" with basic competencies; 1) identify & compare geometric shapes; 2) calculating the surface area of the geometric shape; 3) calculate the volume of the geometric shape. This is what drives the need to develop game-based mathematics learning media.